2013
DOI: 10.1111/clr.12228
|View full text |Cite
|
Sign up to set email alerts
|

Impact of autogenous concentrated bone marrow aspirate on bone regeneration after sinus floor augmentation with a bovine bone substitute – a split‐mouth pilot study

Abstract: There was no significant difference in new bone formation between the test and control group with n = 7. The results may be dominated by the high mineral content of the biomaterial but could nevertheless be valuable for meta-analysis in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
119
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(127 citation statements)
references
References 37 publications
5
119
0
3
Order By: Relevance
“…Despite our findings, xenografts, like certain BBGs primarily used in dentistry, may be slow to degrade [77][78][79] and does not allow for extensive bone regeneration because of its low osteogenic power. 80 However, these materials have been used successfully in numerous clinical and preclinical studies, including guided bone regeneration, 81,82 sinus augmentation 83,84 and socket augmentation, 85,86 suggesting that the present study has important implications in the clinical setting. Furthermore, little is known about the effects of oestrogen deficiency on bone reconstruction procedures.…”
Section: Discussionmentioning
confidence: 94%
“…Despite our findings, xenografts, like certain BBGs primarily used in dentistry, may be slow to degrade [77][78][79] and does not allow for extensive bone regeneration because of its low osteogenic power. 80 However, these materials have been used successfully in numerous clinical and preclinical studies, including guided bone regeneration, 81,82 sinus augmentation 83,84 and socket augmentation, 85,86 suggesting that the present study has important implications in the clinical setting. Furthermore, little is known about the effects of oestrogen deficiency on bone reconstruction procedures.…”
Section: Discussionmentioning
confidence: 94%
“…For vital mineralized bone, these studies reported variable statistical significance. At 3–4 months, new bone formation for BMAC groups with controls [2, 14, 15] using no BMAC was 7.4–12.6% and for the control groups was 9.45–14.3%. At 6 months, new bone formation for BMAC groups [2, 15] was 13.5–14.12% and for control groups was 10.41–13.9%.…”
Section: Resultsmentioning
confidence: 99%
“…At 3–4 months, new bone formation for BMAC groups with controls [2, 14, 15] using no BMAC was 7.4–12.6% and for the control groups was 9.45–14.3%. At 6 months, new bone formation for BMAC groups [2, 15] was 13.5–14.12% and for control groups was 10.41–13.9%. For new bone formation, most studies reported no significant difference between the test and control and between the 3 and 6 months histologic evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been proven that the BMAC method is suitable for isolating cells for sinus augmentation of human MSCs, and that 'making bone' with BBM and the isolated cells is possible (Schmelzeisen et al, 2011). A multicentric sinus augmentation study has been performed to compare these two separation models in patients McAllister et al, 2009;Oshima et al, 2014;Sauerbier et al, 2010aSauerbier et al, , 2010bWildburger et al, 2013); similar cell numbers from the two isolation procedures for cell harvesting were found. Bovine bone mineral was vitalized with the separated cells and inserted into the maxillary sinus.…”
Section: Discussionmentioning
confidence: 98%